The Self-television Concept — Reflections on the Cogni- tive Status of Television. An Analysis of the Meta-television Narration and the Autoreflexive Nature of Television - Bogunia-Borowska, Małgorzata (Culture & Society, 2010)
The new media and new technologies release and provoke socio-cultural changes not only in function of the old media but also in human existence. In the centre of the author’s interest is the concept of “self-television”. Although the role of television in contemporary world is still very significant, the evolution and modernization of television structure is essential. On one hand television structure very quickly reacts to very dynamic socio-cultural processes and challenges and on the other adapts to them. The concept of self-television emphasizes two processes which are responsible for the construction of modern television. One of them is meta-television narration and another is related to the autoreference nature of television. Both of them have caused a series of changes in the television structure which adjust to the cognitive structures of the television viewers. In this sense the television which tries to follow socio-cultural changes reproduces and popularizes the social mechanisms and social rules. In the context of the modern role of television in society it brings up also the problem of confusion of the public and private sphere and public and behind the scene actions which is analyzed in the article. Therefore the main purpose of the article is to research these two main processes which are observed in the construction and development of self-television.